The Role of Investments in Bank Asset Management - Bank Management Committee (New York : The American Bankers Association, 1967)
Successful management of a bank's assets is essentially a matter of strategy. It requires a close familiarity with a great many economic and financial interrelationships, an acute sense of timing and a willingness to move at a time against the trends of the moment.
Study 5: Adopting the portfolio to changing conditions
osc 10/7/17
Loans
Keywords: Bank management